The Influence of Knowledge on Performance Mediated by Human Resources in Micro, Small, and Medium Enterprises (MSMEs) - Eddi Supriadi; Vip Paramarta; Kosasih Kosasih; Farida Yuliaty (Dinasti International Journal of Education Management and Social Science, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in West Java face significant challenges in sustaining their operations amidst digital disruption and increasing market uncertainty. In this environment, knowledge is no longer merely an informational asset but a strategic driver of efficiency, innovation, and customer satisfaction. However, the strategic value of knowledge cannot be fully realized without the support of high quality human resources (HR) capable of interpreting, managing, and applying it in day-to-day business activities. This study aims to examine the influence of knowledge on MSME performance, with HR quality as a mediating variable. Employing a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 93 MSME actors in West Java. The findings reveal that both knowledge and human resource quality significantly influence MSME performance, both directly and indirectly. These results underscore that knowledge management when grounded in capable human resources is a critical strategy for driving competitiveness and sustainable growth among MSMEs in the era of digital transformation.